Acute, sub-acute, sub-chronic and chronic toxicity studies of four important Nigerian ethnomedicinal plants in rats - Abdullah M. Tauheed, Abdullah M.; Mamman, Mohammed; Ahmed, Abubakar (Springer Nature, 2021)
Background: Azadirachta indica, Khaya senegalensis, Anogeissus leiocarpus and Tamarindus indica are important ethnomedicinal plants used for health mitigation since the history of mankind. They are used discretionarily in folkloric medicine on the premise that they are natural products devoid of synthetic preservatives. However, nature endows plants with metabolites for warding off potential attacks from animals and the environment. Some of these metabolites are responsible for toxicity of some plants. Furthermore, drug-induced liver injuries and nephrotoxicity are the leading causes of pharmaceutical attrition of promising drug candidates in clinical trials. Thus, we aimed to evaluate the safety of four ethnomedicinal plants in short-, medium- and long-term usage. Methods: Rats dosed once with 5000 mg/kg extracts of each of these plants served as acute study (AS) while rats dosed daily with 2000 mg/kg for 2, 12 and 14 weeks served as sub-acute (SAS), sub-chronic (SCS) and chronic (CS) studies, respectively. Rats administered distilled water served as the negative control (NC). Results: A. leiocarpus and T. indica significantly reduced percentage weight gain in the SCS compared to the NC. A.leiocarpus significantly (P< 0.05) increased transaminases and alkaline phosphatase in the AS only; and total protein (TP) in the AS, SAS, SCS and CS compared to the NC. K. senegalensis significantly (P< 0.05) increased alanine aminotransferase but significantly (P< 0.05) decreased TP in the AS only compared to the NC. However, A. indica and T. indica significantly (P< 0.05) increased globulin and aspartate transaminase in the CS only. Whereas A. leiocarpus and K. senegalensis significantly (P< 0.05) increased urea and creatinine in the AS than SAS, SCS and CS; Na+ and K+ were significantly higher in the SCS and CS studies compared to the NC. The histological lesions seen ranged from cellular degeneration, congestion, fibrosis to necrosis. Conclusion: Thus, nonlethal, reversible toxic insults occur in short-term usage (AS); while, insidious lethal toxic effects occur in medium-term (SAS) and long-term usage (SCS and CS). The ability of these plant to maintain adequate hematological parameters, bodyweight and absence of mortality may explain free usage of preparations made from these plants in folkloric medicine
Keywords: Aminotransferases; Alkaline phosphatase, Clinicopathology; Kidney function test; Organosomatic index; Toxicity studies; Ahmadu Bello University; ACENTDFB; ACE: Neglected Tropical Diseases and Forensic Biotechnology; Na’imatu A. Sani; Mohammed M. Suleiman